Floating gold grains and nanophase particles produced from the biogeochemical weathering of a gold-bearing ore - Shuster, Jeremiah (2016)
A gold-bearing ore from the San Salvador vein, Capillitas mine, Argentina, was exposed to an enriched, iron- and sulfur-oxidizing bacterial consortium for two months in an experimental system that represented an oxidized, acid-leached weathering environment. Within this laboratory model, the dissolution of metal sulfide minerals by the bacterial consortium liberated gold grains that floated on water. Surficial crevices on grains contained detrital material associated with μm-scale, gold-rich bacteriomorphic structures interpreted to be relics of gold dissolution. The presence of nanophase gold particles, i.e., colloids and octahedral platelets, was attributed to gold reprecipitation. These secondary gold structures suggest that gold dissolution/reprecipitation, i.e., cycling, was occurring concurrently with the bacterially catalyzed dissolution of metal sulfides. The flake-like morphology and small size of gold grains, i.e., high surface area to volume ratio increased by μm-scale surface dissolution textures, would have enhanced their propensity to float. The liberation of buoyant gold grains and secondary gold particles could contribute to rapid gold mobility and dispersion in natural environments.